Skin-specific knockdown of hyaluronan in mice by an optimized topical 4-methylumbelliferone formulation. (1st January 2021) - Steen, Emily H.; Short, Walker D.; Li, Hui; Parikh, Umang M.; Blum, Alexander; Templeman, Natalie; Nagy, Nadine; Bollyky, Paul L.; Keswani, Sundeep G.; Balaji, Swathi
Abstract: Hyaluronan (HA) is abundant in the skin; while HA can be synthesized by the synthases (HAS1-3), HAS2 is the leading contributor. Dysregulation and accumulation of HA is implicated in the pathogenesis of diseases such as keloid scarring, lymphedema and metastatic melanoma. To understand how HA synthesis contributes to skin physiology, and pathologic and fibrotic disorders, we propose the development of skin-specific HA inhibition model, which tests an optimal delivery system of topical 4-methylumbelliferone (4-MU). A design-of-experiments (DOE) approach was employed to develop an optimal 4-MU skin-delivery formulation comprising propylene glycol, ethanol, and water, topically applied to dorsal skin in male and female C57BL/6J wildtype mice to determine the effect on HAS gene expression and HA inhibition. Serum and skin samples were analyzed for HA content along with analysis of expression of HAS1-3, hyaluronidases (HYAL 1-2), and KIAA1199. Using results from DOE and response surface methodology with genetic algorithm optimization, we developed an optimal topical 4-MU formulation to result in ∼70% reduction of HA in dorsal skin, with validation demonstrating ∼50% reduction in HA in dorsal skin. 4-MU topical application resulted in significant decrease in skin HAS2 expression in female mice only. Histology showed thicker dermis in male mice, whereas female mice had thinner dermal layer with more adiposity; and staining for HA-binding protein showed that topical 4-MU resulted in breakdown in HA. Our data suggest a topical 4-MU formulation-based dermal HA inhibition model that would enable elucidating the skin-specific effects of HA in normal and pathologic states.